Legal Review of Immigration Authorities and Handling of Foreign Workers in Indonesia, a Comparison to Immigration Provisions in the United States - Anita Sabara Sutphin (Budapest International Research and Critics University, 2022)
Experts in certain fields are very much needed by Indonesia during the development period. currently being activated, triggering national private companies to bring in foreign workers with certain skills. Their presence is a necessity because Indonesia still needs foreign experts in developing human resources in various economic sectors in Indonesia. In contrast to the United States where all companies in the United States are required to ensure that all employees can work legally. If a person is not a citizen or legal permanent resident in the United States, then they will need a valid work permit known as an Employment Authorization Document to prove eligibility to work in the United States. The focus of the problems studied in this study, namely how is the legal review of immigration authority in handling foreign workers in Indonesia and the United States? and how does the legal authority compare to foreign workers in Indonesia and the United States? The research method used in this study is a comparative qualitative method with a qualitative approach and data analysis used by researchers using qualitative analysis. In practice, law and policy regarding foreign workers, Indonesia has several regulations regarding foreign workers which are frequently updated, until now foreign workers are based on Presidential Regulation No. 34 of 2021 concerning Foreign Workers which is a derivative of the Job Creation Act. Unlike the case with the United States which tends to add federal laws rather than updating the rules regarding applicable Foreign Workers.